2014
DOI: 10.20453/reh.v20i1.1777
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación in vitro del efecto antibacteriano del extracto etanólico de propóleo de Oxapampa - Perú sobre cultivos de Streptococcus mutans (ATCC 25175) y Staphylococcus aureus (ATCC 25923)

Abstract: IntroducciónLa cavidad oral alberga innumerables microorganismos en un ecosistema de complejidad considerable. Estos micro organismos constituyen la flora oral del ser humano, la cual es altamente diversa. Estos microorganismos orales son parte importante en la salud y la enfermedad oral; por lo tanto es de vital importancia buscar nuevas sustancias para ayudar a controlar la proliferación de estos microorganismos.El propóleo es una sustancia compleja constituida por una gran variedad de compuestos químicos, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…The CEs of propolis with the largest zones of inhibition were those from apiaries in Chontabamba, Saylla, Yura, and Oxapampa, with the last being widely studied and showing similar effects in previous studies ( Alemán et al ., 2018 ; Eguizábal & Nakata, 2014 ; Tovalino & Contreras, 2010 ). The boundless vegetation of the Oxapampa valley, where species such as Dictyocaryum lamarckianum (palm tree), Juglans neotropica (Andean walnut), Cyrtocymura scorpioides , Vernonanthura patens ( Kunth), Baccharis latifolia , Cecropia spp., Inga spp., and Pinus tecunumanii (timber tree), combined with the tropical climate of this area ( Muñoz & Del Pilar, 2015 ), offer a variety of active components that are transported by bees to their hives in the form of propolis ( Fernández-Calderón et al ., 2020 ; Okińczyc et al ., 2020 ; Rivera & Mesía, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CEs of propolis with the largest zones of inhibition were those from apiaries in Chontabamba, Saylla, Yura, and Oxapampa, with the last being widely studied and showing similar effects in previous studies ( Alemán et al ., 2018 ; Eguizábal & Nakata, 2014 ; Tovalino & Contreras, 2010 ). The boundless vegetation of the Oxapampa valley, where species such as Dictyocaryum lamarckianum (palm tree), Juglans neotropica (Andean walnut), Cyrtocymura scorpioides , Vernonanthura patens ( Kunth), Baccharis latifolia , Cecropia spp., Inga spp., and Pinus tecunumanii (timber tree), combined with the tropical climate of this area ( Muñoz & Del Pilar, 2015 ), offer a variety of active components that are transported by bees to their hives in the form of propolis ( Fernández-Calderón et al ., 2020 ; Okińczyc et al ., 2020 ; Rivera & Mesía, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition of propolis is closely related to the resins and balsams of the plant sources used to produce it. More than 300 chemical components of propolis have been identified (Barbosa Bezerra et al, 2017;Bryan et al, 2016), and the main groups are waxes, polyphenols (phenolic acids, flavonoids), and terpenoids (Bonamigo et al, 2017;De Freitas et al, 2018;El-Guendouz et al, 2018;Hochheim et al, 2020;Popova et al, 2015;Sve cnjak et al, 2020;Touzani et al, 2019;Zhang et al, 2017). Some research studies have demonstrated an effect of propolis on oral bacteria biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Dogs are considered reservoirs of drug-susceptible bacteria and drug-resistant bacteria such as S. aureus. This has led to research new alternative treatments, one of them being ethanolic extracts of propolis for topical applications, an alternative that has proven to be effective and inexpensive [7]. Exposure of S. aureus to ethanolic extracts of propolis (20% -40%) was effective in these concentrations [8].…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…En el 2009, Mayta-Tovalino y col. evaluaron el efecto antibacteriano del extracto etanólico de propóleo de Oxapampa-Perú, determinaron in vitro su acción antibacteriana frente al Streptococcus mutans (ATCC 25175) y Staphylococcus aureus (ATCC 25923) para enfrentarlas a las soluciones: 10% y 30% y compararlas con los testigos Clorhexidina al 0,12%, 0,05%, Listerine® y agua destilada, mediante el método de Kirby -Bauer (26). El diseño del estudio fue de tipo experimental in vitro.…”
Section: Efecto Antibacteriano Del Propóleounclassified